Knowledge. - Welbourne, Michael (Central problems of philosophy., 2014)
What is it about knowledge that makes us value it more highly than mere true belief? This question lies at the heart of epistemology and has challenged philosophers ever since it was first posed by Plato. Michael Welbourne's examination of the historical and contemporary answers to this question provides both an excellent introduction to the development of epistemology but also a new theory of the nature of knowledge. The early chapters introduce the main themes and questions that have provided the context for modern discussions. The Platonic beginnings, Cartesian individualism and the tripart.